Electric guitar in the Brazilian choro: an analysis of Odeon by Ernesto Nazareth as recorded by Olmir Stocker (Alemão) (Per Musi, 2014)
This article intends to investigate how Olmir Stocker (Alemão) adapts the choro language to the electric guitar. We transcribe and analyze the counterpoint present on the track Odeon, recorded on his album De A a Z in 1995. Based on the definition of the musical genre put forth by Franco FABBRI (1982), we verify the degree to which the musician pushes for innovations that do not cause the choro to lose its distinctive character, thus contributing to the development of a Brazilian language for the electric guitar based on a genre recognized as a symbol of Brazilianness.